Chronopharmacology of Analgesic Effect and Tolerance Induced by Six Narcotic Analgesics in Mice - Yu, Z.-q.; Zhang, C.-l.; Xu, Y.-j.; Chang, M.-j.; Jin, J.-j.; Luo, L.; Li, X.-p.; Liu, D. (Drug Research, 2015)
Narcotic analgesics, especially morphine, exert significantly different effects depending on the time within one day. The objective of this study was to observe whether the dosing time of 6 narcotic analgesics in mice affected their efficacy, pain tolerance and recovery of tolerance. The chronopharmacology of these 6 narcotics was evaluated using a hot-plate model. Maximum possible effect (MPE) of morphine showed a significant 24 h rhythm, which was higher during the dark phase and lower during the light phase (P<0.05). Conversely, MPEs of fentanyl and bucinnazine groups during the light phase exceeded those during the dark phase (P<0.05). Pain tolerance developed after drug administration at 9:00 am or 9:00 pm for 5 days, of which bucinnazine produced lower tolerance at 9:00 am. After a 2-day washout period, the mice rapidly recovered from tolerance at 3:00 pm for 5-day morphine dosing at 9:00 pm, and for fentanyl dosing at 9:00 am. Not all narcotic analgesics displayed significant circadian variations, and the dosing time-dependent effects also depended on the types of narcotics. Therefore, the time of administration is crucial in clinical pain treatment. Chronotherapy may be more effective to relieve pain while reducing side effects.
Keywords: narcotic analgesics; tolerance; chronopharmacology; 24 h rhythm; time of administration